Life cycle of Goeldichironomus holoprasinus goeldi (Diptera: Chironomidae) in laboratory - Zilli, Florencia Lucila (2009)
The larvae of Chironomidae are very important due to their density and role in aquatic food webs. Goeldichironomus holoprasinus Goeldi is one of the most abundant species of Chironomidae in man-made and natural systems, being widely used in water quality assessments. Because of its tolerance to stressing environmental factors, many studies have investigated the effects of stressors on G. holoprasinus anatomy and bionomic attributes. The main aim of this work was to describe G. holoprasinus life cycle attributes in laboratory conditions. The cephalic capsule growth among instars was 1.64 in average (Dyar proportion), whereas the total size growth was continuous. The average room temperature registered was 26 oC (18-33°C). In this conditions the D value (time from oviposition to first imago emergence) was 13 days, whereas the minimum G value (interval from the oviposition to the first progeny of the next generation) was 16 days. The emergence lasted four days, which determined that average G of 18 days. Thus, at registered temperatures G. holoprasinus has a short life cycle.